Tokoh Bisma dalam Dramatari Amba Bisma - Mulyati, Eti; Rusliana, Iyus (LP2M ISBI Bandung, 2020)
ABSTRACTDramatari Amba Bisma is one of the works of Iyus Ruslianan and Eti Mulyati from the results of researchon the art that was performed at the Sunan Ambu Building, on October 28, 2019. The Dramatari wassourced from the Mahabharata and Bharatayuda plays, from the Mahabharata play that sparked the meetingof Amba and Bisma while still on October 28, 2019. girls and young men who differed in their desiresand purpose in life, while from Bharatayuda’s story told about the death of Bhishma in the Bharatayudawar. This article aims to reveal the figure of Bhishma in Amba Bhishma’s drama, Bhishma is one of thecharacters in puppets who are magic and do not want to be crowned as kings for the Hastinapur family,he chose the way of life as a receipt rather than as a king. Because of his life choices, he was determined notto get married. Not only does Bhishma have a very problematic way of life, but many positive qualitiesdeserve to be emulated. The method used is qualitative with a descriptive analysis approach, namelythrough literature study, interviews, and participatory observation. The results obtained from the analysisof Amba Bisma’s dramatari work can be seen by two positive characters in Bisma, namely; 1) sacrifices.2) More loyal to the knight’s oath than to the family that is most dear. During the Baratayuda Bisma waras warlord on the Kurawa side, he was killed by Srikandi’s arrow.Keywords: Bhishma, Dramatari,Mahabharata,BharatayudaABSTRAKDramatari Amba Bisma merupakan salah satu karya Iyus Ruslianan dan Eti Mulyati dari hasilpenelitian karya seni yang di pertunjukan di Gedung Sunan Ambu, pada tanggal 28 Oktober2019. Dramatari tersebut bersumber dari lakon Mahabharata dan Bharatayuda, dari lakonMahabharata menceritkan pertemuan Amba dan Bisma saat masih gadis dan jejaka yangberbeda keingin dan tujuan hidupnya, sedangkan dari lakon Bharatayuda menceritakan tetanggugurnya Bisma dalam perang Bharatayuda. Artikel ini bertujuan ingin mengungkapkantokoh Bisma dalam dramatari Amba Bisma, yakni Bisma merupakan salah satu tokoh dalampewayangan yang merupakan tokoh sakti dan tidak bersedia dinobatkan sebagai raja demikesatuan keluarga Hastinapura, Bisma memilih jalan hidup sebagai resi ketimbang sebagai raja.Hal ini diperkuat dengan keyakinannya, untuk tidak menikah. Bisma tidak hanya memiliki jalanhidup yang sangat problematik, akan tetapi banyak sifat positif yang pantas untuk diteladani.Metode yang digunakan adalah kualitatif dengan pendekatan deskriptif analisis, yaitu melaluistudi pustaka, wawancara, dan observasi partisipasi. Hasil yang diperoleh dari analisis garapandramatari Amba Bisma dapat diketahui dua karakter positif yang ada pada diri Bisma yaitu; 1)suka berkorban. 2) Lebih setia pada sumpah kesatria ketimbang dengan keluarga yang palingdisayangi. Pada perang Baratayuda Bisma sebagai panglima perang di pihak Kurawa menemuiajalnya tertusuk panahnya Srikandi.Kata Kunci: Tokoh Bisma, dramatari, Mahabharata, Bharatayuda